MAKNA SIMBOL MOTIF SONGKET PADA SITUS KOMPLEKS MAKAM KAWAH TENGKUREP - Widia Ningsih; Masyhur Masyhur; Padila Padila (Tanjak: Sejarah dan Peradaban Islam, 2021)
Tengkurep Crater is the burial place of the Palembang Sultanate which was built in 1728 which consists of four cupolas. This research is focused on the meaning of the symbol of the Sognket motif on the site of the Tengkurep Crater tomb complex which can provide information about the development of artistic culture during the Palembang Sultanate. Based on the results of the study, there were four songket motifs and their symbolic meanings found at the Tengkurep Crater Tomb Complex, namely the tumpal motif, the meru motif, the geometric motif and the berante motif. The method used to answer these problems is through observation and literature study. The data that has been collected is then analyzed and conclusions are drawn.